Household violence against women in rural Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The prevalence of household violence against women is high in Bangladesh. Poverty, illiteracy and religious values are usually blamed for such violence. This report assesses the prevalence and determinants of violence against women within marriage and the role of credit program in reducing violence in rural Bangladesh. Three forms of marital violence such as verbal abuse, mental torture and physical assault were focused by using case study method. The report concludes that the risk of marital violence can be significantly reduced by expanding women's participation in credit-based development programs for the poor.